2019
DOI: 10.1001/jamanetworkopen.2019.1156
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Financial Incentives on Patient Use of Mailed Colorectal Cancer Screening Tests

Abstract: Key Points Question Can different forms of financial incentives (unconditional, conditional, or lottery) boost response rates to mailed colorectal cancer screening outreach? Findings In this randomized clinical trial of 897 patients, there was no statistically significant difference in screening response rates at 2 and 6 months between the incentive arms and mailed outreach without incentive. Meaning Different forms of financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 36 publications
1
76
1
Order By: Relevance
“…Tailored materials, such as culturally sensitive brochures or videos, and education, whether in person or in a group setting, also had positive outcomes, but not to the extent of patient navigation or free screening kits. Interestingly, Mehta and colleagues approached CRC screening uptake by providing financial incentives via 3 arms: unconditional, conditional, and lottery [ 81 ]. The unconditional arm was given a $10 gift card along with the FIT kit, while those in the conditional arm received the $10 gift card after completion of the FIT testing if within 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…Tailored materials, such as culturally sensitive brochures or videos, and education, whether in person or in a group setting, also had positive outcomes, but not to the extent of patient navigation or free screening kits. Interestingly, Mehta and colleagues approached CRC screening uptake by providing financial incentives via 3 arms: unconditional, conditional, and lottery [ 81 ]. The unconditional arm was given a $10 gift card along with the FIT kit, while those in the conditional arm received the $10 gift card after completion of the FIT testing if within 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, this would still allow for the possibility that once individuals decided to do the screening, they would finish it for reasons unrelated to monetary incentives. However, this reciprocity motive would also contradict evidence showing that noncontingent incentives underperform compared with contingent incentives in promoting compliance with health procedures . If noncontingent incentives elicited reciprocity to a significant extent, these would produce similar completion rates compared with contingent incentives.…”
Section: Discussionmentioning
confidence: 90%
“…There is consistent evidence that noncontingent (versus contingent) incentives are less effective in promoting healthcare compliance . In fact, Mehta et al . have shown that a single initial contingent $10 incentive did not increase colorectal cancer screening, by comparison with a control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations